RegTech on Crypto FinTech: What Needs to be Done and Its Implications for the Anti-Money Laundering Mechanism - Fajri, Kharisma Fatmalina; Faachrezzi, Bima Rafly; Kurniawan, Bagja (Otoritas Jasa Keuangan, 2024)
Crypto laundering has become a significant threat in Indonesia since 2015, particularly through digital payment systems. Despite efforts to combat this threat using Regulatory Technology (RegTech), the outcomes have been largely ineffective. This study expands on previous research exploring the causes of RegTech's ineffectiveness and seeks to provide policy recommendations based on RegTech provider perspectives, for Indonesian regulators to enhance crypto laundering mitigation through RegTech. The research employed an exploratory-inductive methodology, utilising primary data from semi-structured interviews with AML operating system specialists. The data were transcribed and thematically analysed using NVivo software. The findings reveal six key themes for improving RegTech effectiveness: (1) AML mechanisms tailored to various sizes of Crypto FinTechs; (2) Access to PEP data by RegTech providers; (3) Clear classification of RegTech; (4) Strengthened collaboration between regulators and RegTech providers; (5) Regulator-led education initiatives for Crypto FinTechs; and (6) The establishment and enforcement of sanctions. These insights hold significant implications for regulatory policies aimed at preventing crypto laundering through RegTech and contribute to the application of Rational Choice and Butterfly Effect theories in understanding crypto laundering as a criminal phenomenon.